Range of Motion Exercise with a Jagged Rubber Ball can Improve Upper Extremity Muscle Strength in Stroke Patients - Sri Pradnyani; IGA Ari Rasdini; V.M.Endang S.P Rahayu; Made Wedri (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
The provision of ROM exercises with jagged rubber balls can increase the strength of the hand muscles of stroke patients. This study aimed to determine the effect of ROM exercises with serrated rubber balls on increasing the strength of the upper extremity muscles in stroke patients. Design of pre-test and post-test with one group. Selection of a nonprobability sample with a purposive sampling type, the sample is 11 people in the Tabanan General Hospital in the inpatient ward in the stroke corner and outpatient ward. The average hand muscle strength in ROM exercises with a jagged rubber ball was distinguished by the male and female sex, namely before 12.5 and 12.7 after treatment, the average hand muscle strength was 15.2 and 15.6. Based on the mean value, patients with stroke experienced an increase in the normal category as measured using a hand dynamometer before and after giving therapy exercises by holding a jagged rubber ball. The test results of the analysis of the paired sample test above obtained a sig value of 0.000. In conclusion, there is a significant effect of ROM training by holding a serrated rubber ball on increasing upper limb muscle strength in stroke patients at Tabanan Hospital in 2022. It is hoped that it can be used as a nursing intervention to improve function in stroke and revive brain control over muscles. Keywords: strokes; muscle strength; serrated rubber ballLatihan Range of Motion Dengan Bola Karet Bergerigi Dapat Meningkatkan Kekuatan Otot Ekstremitas Atas Pada Pasien StrokeABSTRAK Pemberian latihan ROM dengan bola karet bergerigi dapat meningkatkan kekuatan otot tangan pasien stroke.Tujuan penelitian untuk mengetahui pengaruh latihan ROM dengan bola karet bergerigi terhadap peningkatan kekuatan otot ekremitas atas pada pasien stroke.Desain pre-test post-test with one group. Pemilihan sampel nonprobability dengan jenis purposive sampling, sampel adalah 11 orang di RSUD Tabanan pada ruang rawat inap di ruang stroke corner dan rawat jalan. Rata-rata kekuatan otot tangan dalam latihan ROM dengan bola karet bergerigi dibedakan dengan jenis kelamin laki laki dan perempuan yaitu untuk sebelum 12,5 dan 12,7 sesudah perlakuan rata-rata kekuatan otot tangan yaitu 15,2 dan 15,6. Berdasarkan nilai rata rata, pasien dengan stroke mengalami peningkatan kategori normal diukur menggunakan alat ukur hand dynamometer sebelum dan sesudah pemberian latihan terapi menggemgam bola karet bergerigi. Hasil uji analisis uji paired sampel test diatas, didapatkan nilai sig yaitu 0,000. Simpulan terdapat pengaruh yang signifikan dari latihan ROM dengan menggenggam bola karet bergerigi terhadap peningkatan kekuatan otot ekremitas atas pada pasien Stroke di RSUD Tabanan tahun 2022.Diharapkan dapat dijadikan salah satu intervensi keperawatan untuk meningkatkan fungsional pada stroke dan membangkitkan kembali kendali otak terhadap otot. Keywords: stroke; kekuatan otot; bola karet bergerigi